The value of life in the Jewish tradition: towards understanding Jewish bioethics - Barilan, Michael (Studia Bioethica, 2011)
Jewish valuation of life is borne out by different dimensions of appraisal. The first is 'recognition respect' of the vulnerability of life and loving care that protects it. This is the fundament of Jewish virtue ethics. Homicide is considered the worst of evils. Special regard to the protection of human life leads to the paradoxical outcome that sometimes respect for life entails the loss of life. This is true not only with regard to the protection of biological life, as in situations of self-defense, but also, in circumstances that call for protection of dimensions of life that are no less valuable morally than life itself – the sexual integrity of people, their dignity and their protection from unremitting suffering. Unabashed devotion to the creation of new life and acceptance of some risk and suffering for the sake of procreation embody one more dimension of valuing life and of acting out the image of God in humans. The fourth dimension is a sensibility for all that is unique and joyful within earthly life as such.